The hypocrisy – changing the vices into virtues - Tamaș, Iosif (Buletin de psihiatrie integrativa, 2021)
This article focuses on identifying and presenting the roots and consequences of hypocrisy within the hidden pathological features of the human being. Hypocrisy belongs to the hypocrite, that is, to the individual in his ontic integrity as an immortal body, spirit, and soul. In this respect this scientific discourse has its place within the religious space as well, at the spiritual level of the perfect process of creation, where the new spiritual individual is always active; At the empirical, scientific and material level of the human activity there is only the ideological individual, proficient or not, just like in the unfortunate case of the priest – sacerdos in aeternum who became professor after he jumped the fence of the house and he got into the yard of the University, with the passport in his pocket of course. We will approach the subject strictly through the paradigm of the theological-philosophical discourse, framed by the constitutive horizon of moral philosophy (philosophical ethics), which is defined as the second strand of bioethics as a modern science, according to the traditional medical ethics (1). Within this paper we will look at the following points: the formalism of religious hypocrisy; the blindness of the hypocrite as a pathological manifestation and finally about the availability as a permanent risk of hypocrisy.